Safety, efficacy and prognostic impact of immune checkpoint inhibitors in older patients with genitourinary cancers. Issue 7 (September 2020) - Schulz, Gerald Bastian; Rodler, Severin; Szabados, Bernadett; Graser, Annabel; Buchner, Alexander; Stief, Christian; Casuscelli, Jozefina
Abstract: Introduction: Immunosenescence might impact immunotherapy (IT) in patients with advanced age. However, pivotal studies were not powered for this clinical question. Our aim is to explore toxicity (primary objective) and activity (secondary objective) of immune checkpoint inhibitors (ICIs) in patients with renal cell (RCC) and urothelial carcinoma (UC) older than 75 years compared to the younger population. Patients and Methods: Patients treated at our tertiary care Uro-oncology Department with atezolizumab, pembrolizumab, nivolumab or ipilimumab were retrospectively analyzed. Immune-related adverse events (irAEs) were determined and graded using the Common Terminology Criteria for Adverse Events (CTCAE v.4.0). Disease Control rate (DCR) was assessed according to Response Evaluation Criteria in Solid Tumors (RECIST v1.1). IrAEs and DCR were compared between patients ≥75 vs. <75 years, chi-squared test. Impact of age and other key clinical parameters on irAEs and DCR were tested in a binary logistic regression employing a backward selection. Impact of irAEs on oncological prognosis was assessed in log-rank and Cox regression analyses. Results: We included 99 patients treated between 11/2015 and 01/2019. Frequency of irAEs (36.4% vs. 39.4%) and DCR (59.4% vs. 41.0%) was comparable between patients ≥75 vs. <75 years. Advanced age was not associated with irAEs or worse DCR. IrAEs occurrence correlated with better disease-specific survival in the univariate and multivariate analyses. IrAEs could be successfully treated with corticosteroids in 78.9% of cases. Conclusions: ICIs seem to be both safe and efficacious in an aging population with metastatic RCC or UC. Occurrence of irAEs predicted better prognosis. Highlights: Elderly and patients with low performance status are underrepresented in approval trials for different checkpoint-inhibitors. However, toxicity and disease control are comparable to younger patients. Immune related toxicity correlates with improved oncological survival. Advanced age should not be an impediment for immune checkpoint inhibitor therapy ofmetastatic RCC or UC.